2005
DOI: 10.1111/j.1365-2958.2005.04647.x
|View full text |Cite
|
Sign up to set email alerts
|

A directed screen for chlamydial proteins secreted by a type III mechanism identifies a translocated protein and numerous other new candidates

Abstract: SummaryChlamydiae are strict intracellular parasites that induce their internalization upon contact with the host cell and grow inside an intracellular compartment called an inclusion. They possess a type III secretion (TTS) apparatus, which allows for the translocation of specific proteins in the host cell cytosol. In particular, chlamydial proteins of the Inc family are secreted to the inclusion membrane by a TTS mechanism; other TTS substrates are mostly unknown. Using a secretion assay based on the recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 36 publications
7
145
1
1
Order By: Relevance
“…Moreover, the other genes of this locus are arranged in operons (24) and predicted to encode important members of the T3SS apparatus, including the ATPase, chaperones, and membrane components (16). There is evidence that CT668, CT670, and CT671 are secreted proteins (47,51), and yet given their gene order they could represent mobile components of the T3SS apparatus. Indeed, CT670 contains an YscO-like domain raising the possibility that CT670 and CT671 correspond to the secreted Yersinia apparatus components YscO and YscP, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the other genes of this locus are arranged in operons (24) and predicted to encode important members of the T3SS apparatus, including the ATPase, chaperones, and membrane components (16). There is evidence that CT668, CT670, and CT671 are secreted proteins (47,51), and yet given their gene order they could represent mobile components of the T3SS apparatus. Indeed, CT670 contains an YscO-like domain raising the possibility that CT670 and CT671 correspond to the secreted Yersinia apparatus components YscO and YscP, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the family of Inc-proteins, other chlamydial proteins secreted into the inclusion membrane have been identified (14,15). Moreover, proteins targeted into the host-cell cytosol have been described (16)(17)(18).…”
mentioning
confidence: 99%
“…Moreover, these investigators showed proteins from Cp. pneumoniae and C. trachomatis, all of which had in common the presence of a large hydrophobic domain, to be secreted by a S. flexneri or Yersinia enterocolitica type III secretion machinery [9,35,36].…”
Section: Introductionmentioning
confidence: 99%